Mauritius - Investment Climate Assessment - World Bank (World Bank, 2012)
This Investment Climate Assessment (ICA) uses a robust methodology that draws on a representative sample of 484 formal firms and 120 informal establishments. The sample covers small-medium enterprises (SMEs) and large firms in both manufacturing and services. Weights were used in the analysis of the data to ensure full representativeness of the results. Although the sample is large, sample non?response could invalidate the results of the analysis-especially for more sensitive questions on corruption, taxes, or sales. In order to reduce such possibilities, strict quality control procedures have been applied during the data collection process. These controls led to an overall response rate of above 90 percent.